De-standardization and gender convergence in work–family life courses in Great Britain: A multi-channel sequence analysis. (December 2015) - McMunn, Anne; Lacey, Rebecca; Worts, Diana; McDonough, Peggy; Stafford, Mai; Booker, Cara; Kumari, Meena; Sacker, Amanda
Abstract: This study addresses the question of de-standardized life courses from a gender perspective. Multi-channel sequence analysis is used to characterise the domains of work, partnership and parenthood in combination across the adult life courses of three birth cohorts of British men and women between the ages of 16 and 42. Three research questions are addressed. First, we examine whether there is evidence of increasing between-person de-standardization (diversity) and within-person differentiation (complexity) in work and family life courses across cohorts during the main childrearing years. Second, we investigate whether men's and women's work–family life courses are converging over time. Finally, we assess the link between educational attainment and work–family life courses across cohorts. Data are from the MRC National Survey of Health and Development 1946 birth cohort ( n = 3012), the National Child Development Study 1958 birth cohort ( n = 9616), and the British Cohort Study 1970 birth cohort ( n = 8158). We apply multi-channel sequence analysis to group individuals into twelve conceptually-based work–family life course types. We find evidence of growing between-person diversity, across cohorts, for both women and men. In addition, partnership trajectories are growing more complex for both genders, while parental biographies and women's work histories are becoming less so. Women's and men's work–family life courses are becoming increasingly similar as more women engage in continuous full-time employment; however, life courses involving part-time employment or a career break remain common for women in the most recent cohort. Continuous, full-time employment combined with minimal family ties up to age 42 emerged as the most common pattern for women and the second most common for men in the 1970 cohort.